Pro PHP Refactoring - Trucchia, Francesco; Romei, Jacopo (Apress : Imprint: Apress, 2010)
Many businesses and organizations depend on older high-value PHP software that risks abandonment because it is impossible to maintain. The reasons for this may be that the software is not well designed; there is only one developer (the one who created the system) who can develop it because he didn't use common design patterns and documentation; or the code is procedural, not object-oriented. With this book, you'll learn to identify problem code and refactor it to create more effective applications using test-driven design.